2008
DOI: 10.1177/000313480807401005
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Prophylaxis in Blunt Traumatic Intracranial Hemorrhage: A Retrospective Review

Abstract: There are few data in the literature on venous thromboembolic (VTE) prophylaxis for the traumatic population with intracranial hemorrhage (ICH). We reviewed our institutional experience and compared the incidence of deep vein thrombosis and pulmonary embolism in patients with ICH receiving either early prophylaxis (<72 hours from admission) or late prophylaxis (>72 hours from admission), and the respective incidences in progression of intracranial hemorrhage. We identified 124 patients for this study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
0
32
1
Order By: Relevance
“…Three other retrospective reviews found somewhat higher rates of VTE that ranged from 7.3% to 14%. 21,54,57 Summary of literature can be found in Table 1; see Table 2 for risk of bias assessment of RCTs based on the Cochrane Collaboration tool. 26 Only seven of the 18 nonrandomized cohort studies reviewed were deemed "low risk" for bias according to Newcastle-Ottawa Scale (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three other retrospective reviews found somewhat higher rates of VTE that ranged from 7.3% to 14%. 21,54,57 Summary of literature can be found in Table 1; see Table 2 for risk of bias assessment of RCTs based on the Cochrane Collaboration tool. 26 Only seven of the 18 nonrandomized cohort studies reviewed were deemed "low risk" for bias according to Newcastle-Ottawa Scale (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…There is currently insufficient research to produce formal clinical guidelines on optimal timing of VTEp. 9,21 In 2002, the Eastern Association for the Surgery of Trauma (EAST) recommended that the safety of VTEp, both low-molecular-weight heparin (LMWH) and unfractionated heparin (UFH) in TBI was not established and VTEp administration should be tailored to each patient. 22 Similarly, both the American College of Chest Physicians (ACCP) and Brain Trauma Foundation (BTF) recommend VTEp in lieu of mechanical prophylaxis as soon as possible after sustaining a TBI, but could not recommend a specific time frame within which VTEp can be safely administered.…”
mentioning
confidence: 99%
“…Although studies to this point had largely concentrated on the act of anticoagulation by itself, the field advanced when Depew et al compared the safety and efficacy profile of LMWH versus UH in 2008. 18 The authors were unable to show a difference between the two anticoagulants regarding the incidence of progression (3%) after initiation before or after 72 hours postinjury, or the incidence of VTE (13 and 11%, respectively) in 124 TBI patients. What is perhaps most compelling about these results, though, is the study's implicit stipulation that the act of anticoagulation was appropriate and it was only the class of medication that was important.…”
Section: Pharmacologic Prophylaxis In the General Traumatic Brain Injmentioning
confidence: 92%
“…The only reports on this field over the next several years would be descriptive studies in 2007 (Cothren et al, 2007) and 2008 (Depew et al, 2008). Cothren and colleagues published their experience with a new anticoagulant, dalteparin, and its safety and efficacy in VTE prevention in 743 polytrauma patients after its initiation a mean of 3.3 days after injury.…”
Section: Anticoagulation After Tbi As a Homogenous Populationmentioning
confidence: 99%
“…The generalizability of this study was limited by decreased compliance with the anticoagulation regimen in the sample (only 74%), a lack of reporting on the timing of dalteparin use for the TBI subgroup, and the fact that this low-molecular-weight heparin has not been adopted as a standard pharmacologic intervention for VTE prevention in non-brain-injured trauma patients. Similarly, the Depew group found TBI progression rates of 3%, whether anticoagulation with enoxaparin or unfractionated heparin was started before or after 72 h in 124 TBI patients, and nearly identical rates of VTE of 13% and 11%, respectively (Depew et al, 2008). The exact times of anticoagulant initiation were not described, so it is impossible to say if they were close enough to have resulted in similar point estimates.…”
Section: Anticoagulation After Tbi As a Homogenous Populationmentioning
confidence: 99%